A Lost Bullet in the Coronary Sinus: A Cautionary Tale - Halicek, Martin; Alslaim, Hossam; Shukla, Mrinal; Freedman, Arthur M.; Bates, William B.; Patel, Vijay S.; Weintraub, Neal L.; Winkler, Michael (International Journal of Angiology, 2022)
We present a case of venous bullet embolism to the right atrium following a gunshot wound (GSW) to the abdomen. A 53-year-old male presented after a GSW to the abdomen. His workup included a computed tomography (CT) scan demonstrating an aortic injury with aortocaval fistula. A radio-opaque object consistent with a bullet was visualized in the right atrium. First, this case details an important decision, choice of surgery versus an interventional approach. After repair of the aortocaval fistula, the patient underwent a planned attempt to extract the bullet through a right lateral thoracotomy approach utilizing cardiopulmonary bypass to facilitate a right atriotomy. Intraoperatively, the team was not able to localize the bullet in the right atrium despite fluoroscopic evaluation. A postoperative CT scan demonstrated that the bullet had migrated into the coronary sinus. Lastly, this case demonstrates successful positioning maneuvers to dislodge the bullet out of the heart and into the inferior vena cava, allowing for the endovascular extraction of the bullet.
Keywords: bullet embolism; coronary sinus; foreign object; endovascular extraction